2017
DOI: 10.1101/191668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Titan cells formation inCryptococcus neoformansis finely tuned by environmental conditions and modulated by positive and negative genetic regulators

Abstract: The pathogenic fungus Cryptococcus neoformans exhibits morphological changes in cell size during lung infection, producing both typical size 5 to 7 µm cells and large titan cells (> 10 µm and up to 100 µm). We found and optimized in vitro conditions that produce titan cells in order to identify the ancestry of titan cells, the environmental determinants, and the key gene regulators of titan cell formation. Titan cells generated in vitro harbor the main characteristics of titan cells produced in vivo includi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
(5 reference statements)
2
12
0
Order By: Relevance
“…Only one protein, CNAG_05312, had both an Nterminal signal peptide and a GPI-anchor indicative of plasma membrane association. These secreted peptides were previously reported to play critical roles in C. neoformans virulence (61)(62)(63)(64)(65). Taken together, these results revealed that C. neoformans melanin granules are indeed intimately associated with proteins that employ both a conventional and non-conventional secretory pathway for regulation, and which may be involved with structural and/or functional properties of the cryptococcal eumelanin.…”
Section: Neoformans Melanin Is Molecularly Associated With Non-polsupporting
confidence: 63%
“…Only one protein, CNAG_05312, had both an Nterminal signal peptide and a GPI-anchor indicative of plasma membrane association. These secreted peptides were previously reported to play critical roles in C. neoformans virulence (61)(62)(63)(64)(65). Taken together, these results revealed that C. neoformans melanin granules are indeed intimately associated with proteins that employ both a conventional and non-conventional secretory pathway for regulation, and which may be involved with structural and/or functional properties of the cryptococcal eumelanin.…”
Section: Neoformans Melanin Is Molecularly Associated With Non-polsupporting
confidence: 63%
“…We noted at 24 h post infection there were rare enlarged yeast cells within the nose turbinates and ears (Fig. 4C-G) whose cell body diameter is above 10 μm, and therefore can be consider titan cells (3032). The finding of titan cells in the nose of mice is concordant with Lima et al ., (33) which found enlarged cells in noses of guinea pigs after some days of infection.…”
Section: Resultsmentioning
confidence: 91%
“…Virulence did not correlate with the ability to grow in vitro in either nutrient-rich and limited nutrient conditions, at low and high temperatures (30°C and 37°C) (Supplemental Figure 3). Using two previously described methods (13, 14), we found that virulence was also not associated with the ability to form titan cells in vitro (Supplemental Table 1). However, we observed a trend where low virulence strains formed more titan cells than high and intermediate virulence strains when grown in DMEM media supplemented with serum (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…To induce the formation of titan cells in vitro , two previously described methods were used (13, 14). For the first method (13), C. neoformans cells from a YPD agar plate were transferred to 10 ml YPD broth medium in a T25cm3 flask (TPP, Switzerland), grown at 30°C for 22 h with shaking (150 rpm), washed with sterile double distilled water and cell number enumerated with a hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation